Fisetin reverses the negative effect of Lambda-Cyhalothrin on the maturation process of porcine oocytes in vitro by downregulating GRP78 levels - Xiu-wen Yuan; Jia-jun Ren; Neng-hao Cao; Xue-rui Yao; Xing-wei Liang; Nam-hyung Kim; Yong-nan Xu; Ying-hua Li (Ecotoxicology and Environmental Safety)
Lambda-Cyhalothrin (LCT), a potent insecticide, is renowned for its efficacy, rapid onset, and broad-spectrum insecticidal activity. With rising annual demand for LCT, environmental concerns have similarly intensified. Nevertheless, its impact on mammalian reproduction, specifically oocytes, and possible mitigation strategies, remains insufficiently understood. This research evaluated the effects of varying LCT concentrations (25, 50, 100 μM) on the in vitro maturation of porcine oocytes, revealing that LCT exposure markedly hindered oocyte maturation and subsequent developmental potential. Fisetin (FIS), a natural flavonoid found in numerous fruits and vegetables, exhibits robust antioxidant, anti-inflammatory, and neuroprotective properties. Notably, when different concentrations of FIS were incorporated into the culture medium of LCT-exposed oocytes, it mitigated LCT-induced toxicity. FIS supplementation significantly enhanced antioxidant capacity, improved endoplasmic reticulum (ER) and mitochondrial functions, and reduced apoptosis in comparison to the LCT-exposed group. Key markers, including the ER stress protein GRP78 (Control: 1.00 vs. LCT: 1.75 ± 0.08, P < 0.001; vs. LCT + FIS: 1.37 ± 0.07, P < 0.001) and autophagy marker LC3B (Control: 1.00 vs. LCT: 1.50 ± 0.32, P < 0.05; vs. LCT + FIS: 1.18 ± 0.16, P > 0.05), were significantly reduced in the FIS-treated oocytes. These results suggest that LCT compromises mitochondrial and ER function in oocytes through the upregulation of GRP78, while FIS supplementation effectively counteracts this toxicity, providing protection against LCT-induced damage. This study underscores FIS’s potential as a protective agent in alleviating LCT-related reproductive toxicity.